Uso de camalhões de base larga como alternativa para o cultivo de soja em terras baixas - Rosso, Ricardo Benetti (2017)
The Rio Grande do Sul (RS) state has 5,4 millions of meadows hectares or low lands, being the rice cultivation its main agricultural activity. This cultivation has faced problems, wich we can highlight the weeds control and the high production cost. Looking for new alternatives, it has been introduced the cultivation rotation in these areas, mainly with the soy cultivation. However, cause of the physical characteristics of these grounds, mainly the poor drainage, the plants present susceptibility to the hydric excess. It has been necessary the water table level demotion, through an efficient drainage, so that the cultivation can reach its productive potential. In this sense, it was realized a research with the goal to evaluate the viability of the soy cultivation in low lands, using different drainage techniques: the broad bed furrow and superficial drainage for the water table level demotion. From this goal, it was performed two experiments, in São João do Polêsine city (RS), on the 2014/2015 and 2015/2016 crops. The first one, in both crops, used different drainage techniques, constituted by three broad bed furrow of different dimensions and the superficial drainage, and two soy cultivations: the BMX Potência RR and the TEC IRGA 6070 RR. The second experiment, on the 2015/2016 crop, used five levels of the water table fixed heights of 0,10; 0,20; 0,30; 0,40 and; 0,50 meters and two soy cultivation: BMX Potência RR and the TEC IRGA 6070 RR. On both experiments, during the cultivation development, it was realized evaluations of the phonological variables, yield components, water table level depth and obtained the climatological data. The results demonstrate that the best production was obtained with the 7,5 and 15 meters of broad bed furrow on the 2014/2015 and 2015/2016 crops. The SEW30 (Sum excess water) and IDS (Stress Daily Index) indexes demonstrate that the broad bed furrow is most efficient in the water table level demotion, wich can be highlighted the 7,5 meters broad bed furrow. The water table level depth is technically viable to be used as a reference for the SEW30 index. The 7,5 meters broad bed furrow has economic viability cause of its productive stability and economic result, being the best alternative for the soy cultivation in low lands areas.